2009
DOI: 10.1016/j.expneurol.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction after experimental febrile seizures

Abstract: While the majority of children with febrile seizures have an excellent prognosis, a small percentage are latter discovered to have cognitive impairment. Whether the febrile seizures produce the cognitive deficits or the febrile seizures are a marker or the result of underlying brain pathology is not clear from the clinical literature. We evaluated hippocampal and prefrontal cortex function in adult rats with a prior history of experimental febrile seizures as rat pups. All of the rat pups had MRI brain scans f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 55 publications
16
105
1
Order By: Relevance
“…In particular, a loss of distal dendritic inhibition in seizure rats may affect spatial coding by a direct entorhinal to CA1 distal-dendritic excitation (Brun et al, 2008;Leung, 2011). Abnormal place cell activity was found in animals with early-life seizures (Dube et al, 2009(Dube et al, , 2010. Attenuation in GABA B R function may be a critical component of epilepsy, and it may participate in a role of ''seizures beget seizures'' (Tsai et al, 2008).…”
Section: Significance and Implications Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a loss of distal dendritic inhibition in seizure rats may affect spatial coding by a direct entorhinal to CA1 distal-dendritic excitation (Brun et al, 2008;Leung, 2011). Abnormal place cell activity was found in animals with early-life seizures (Dube et al, 2009(Dube et al, , 2010. Attenuation in GABA B R function may be a critical component of epilepsy, and it may participate in a role of ''seizures beget seizures'' (Tsai et al, 2008).…”
Section: Significance and Implications Of Resultsmentioning
confidence: 99%
“…As a model of febrile seizures, hyperthermia-induced seizures in immature rats (Baram et al, 1997) were found to increase longterm seizure susceptibility and induce spontaneous seizures (Dube et al, 2010), without significant cell loss or sustained brain damage (Dube et al, 2000). Additionally, long-term behavioral changes have been reported after hyperthermic seizures (Chang et al, 2003;Dube et al, 2000Dube et al, , 2009Dube et al, , 2010. Long-term physiological changes after febrile seizure models include alteration of intrinsic membrane currents and an increased in GABA A receptor-mediated transmission in hippocampal slices in vitro (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, it is more difficult to discern the relationship of the epilepsy and the cognitive defects (122). Temporal lobe or limbic seizures propagate through the same neuronal pathways that are engaged in learning and memory processes (111). Thus, seizures might directly cause such problems; alternatively, the abnormalities that result in the seizures might independently provoke cognitive dysfunction.…”
Section: Cognitive Vulnerability During Agingmentioning
confidence: 99%
“…The repeated-FS also caused long-lasting deficits in synaptic plasticity in CA1 pyramidal cells and reduced tyrosine phosphorylation of the NMDA-receptor subunit NR2A (96). Recently, an abnormal firing rate and poor stability of hippocampal CA1 place cells have been suggested as a basis for the deficits in eFS-induced hippocampal-dependent memory (97).…”
Section: Do Fs Affect the Behavior In Later Life?mentioning
confidence: 99%
“…Furthermore, the development of noninvasive methods such as MRI (97) to detect the future effects of FS on hippocampal malfunction is required.…”
Section: Do Fs Affect the Behavior In Later Life?mentioning
confidence: 99%